2010
DOI: 10.3390/nu2070652
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits of Nut Consumption

Abstract: Nuts (tree nuts and peanuts) are nutrient dense foods with complex matrices rich in unsaturated fatty and other bioactive compounds: high-quality vegetable protein, fiber, minerals, tocopherols, phytosterols, and phenolic compounds. By virtue of their unique composition, nuts are likely to beneficially impact health outcomes. Epidemiologic studies have associated nut consumption with a reduced incidence of coronary heart disease and gallstones in both genders and diabetes in women. Limited evidence also sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
443
1
16

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 619 publications
(466 citation statements)
references
References 151 publications
6
443
1
16
Order By: Relevance
“…Nuts are high in monounsaturated fatty acids, fiber, minerals, vitamins and many bioactive compounds; all these nutrients may partly explain the beneficial effects on health that nuts have been shown to exert [3,4]. The frequency of nut consumption has been inversely related to several chronic prevalent conditions, such as diabetes, hyperlipidemia, hypertension, obesity, metabolic syndrome, cancer, and CHD, among others [5,26]. These inverse associations can be influenced by various mechanisms: nuts improve the blood lipid profile [6] and appear to decrease insulin resistance [8], and there is also evidence suggesting that they can modulate inflammation [35], oxidative stress [36], and endothelial function [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuts are high in monounsaturated fatty acids, fiber, minerals, vitamins and many bioactive compounds; all these nutrients may partly explain the beneficial effects on health that nuts have been shown to exert [3,4]. The frequency of nut consumption has been inversely related to several chronic prevalent conditions, such as diabetes, hyperlipidemia, hypertension, obesity, metabolic syndrome, cancer, and CHD, among others [5,26]. These inverse associations can be influenced by various mechanisms: nuts improve the blood lipid profile [6] and appear to decrease insulin resistance [8], and there is also evidence suggesting that they can modulate inflammation [35], oxidative stress [36], and endothelial function [37].…”
Section: Discussionmentioning
confidence: 99%
“…There is consistent evidence to suggest that the consumption of nuts has a beneficial effect on cardiovascular health, and this effect is attributable to their unique nutritional composition [5]. A pooled analysis of four large-scale observational studies showed that subjects in the highest nut consumption categories had an approximately 35% reduced risk of incident coronary heart disease (CHD) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a diet with increased PUFA from walnuts is also linked to longterm beneficial effects on type II diabetes (Tapsell et al 2009). Dietary walnut fingerprinting using HPLC-q-ToF-MS analysis characterized some urinary biomarkers, such as fatty acids metabolites, (Garcia-Aloy et al 2014) and positive effects of walnut consumption on inflammatory processes, vascular reactivity, glycemic control (Ros 2010), and oxidative stress (Zhao et al 2014) were described. However, walnuts also can be responsible for food-induced allergies, an emergent public health problem, and techniques to detect and characterize J. regia and J. nigra allergens have been developed (Costa et al 2014).…”
Section: Metabolomics Workmentioning
confidence: 99%
“…Nuts have a high total fat content (mostly as mono-and polyunsaturated fat), ranging from 46% in cashews and pistachios to 76% in macadamia nuts, and provide 20-30 kJ per gram [7]. They are also rich in protein, fiber, vitamins, minerals, phytosterols, and polyphenols [8]. Following the approval of a qualified health claim by the Food and Drug Association (FDA) supporting the inclusion of 1.5 ounces (42 g) walnuts in the daily diet [9], several agencies including the American Heart Association (AHA) and the Academy of Nutrition and Dietetics (AND) recommend the inclusion of nuts in the daily diet to further heart health [10,11].…”
Section: Introductionmentioning
confidence: 99%